Quality of life, social support, and adherence in female patients with thyroid disorders - Eliza Kollerits; Ágnes Zsila; Balázs Matuszka (BMC, 2023)
Abstract Background According to the 2010 European Health Interview Survey, 51% of women in Hungary have a chronic disease, and is among the poorest quartile in the EU countries. Thyroid diseases affected more than 650,000 women in 2021 based on a recent report by the Hungarian Central Statistical Office. Despite the high prevalence rates, quality of life in these patients is scarcely researched in Hungary. To fill this gap, this study aims to explore the associations of the quality of life of thyroid patients in Hungary with social support and adherence. Methods A cross-sectional study was conducted via an online questionnaire. Data from 885 female Hungarian thyroid patients with pharmacological treatment (M = 35.6 years, SD = 10.7, age range: 18-73 years) were analyzed. Participants were divided into two patient groups based on the type of thyroid disorder: hypothyroidism (n = 824; 93.1%) and hyperthyroidism (n = 61; 6.9%). Group comparisons, correlations, and a mediation model were performed to explore differences between thyroid patients. Results No differences were found between patients with different types of thyroid disorders in quality of life, adherence, and social support. Consistent, weak associations were found between quality of life and social support in both patient groups. Higher perceived social support partially explained the relationship between adherence and life quality in thyroid patients.  Conclusions No substantial differences were found between patients with different types of thyroid disease in mental well-being indicators. These patients are psychologically more vulnerable and need a socially supportive environment to recover, because higher adherence is associated with a better quality of life, and social support can facilitate this process.